Quality of Services in the Secondary Educational Organizations of Bangladesh: An Evaluation by Secondary Graduates - Md. Shafikuzzaman Joarder; Wardatul Akmam; Mohammad Kais Shaikh; Md. Nazmul Hoque (CV. Literasi Indonesia, 2022)
Despite the burgeoning quantitative progress in tertiary and pre-tertiary levels, popular discourses render a growing concern that the quality of education has deteriorated over the years in Bangladesh. In identifying problems of the educational system in Bangladesh, a majority of previous macro-level studies adopted the approaches of policy-makers, NGOs, international organizations, and other intervening authorities. This study, in distinction, tries to explore the issue from a micro-perspective – students’ views regarding the quality of educational services they received in colleges and high schools, which makes it unique. Using a cross-sectional survey research design, data were collected from 114 first-year students from the University of Rajshahi, Bangladesh. Findings show that regardless of having good teachers, classrooms, and other facilities, students were heavily dependent on private tuition at the pre-tertiary education level. The services and facilities offered by the colleges of the respondents were of better quality than that of their high schools. Schools/colleges in district towns/divisional cities offer better quality services/facilities than those located at the union/village level. Respondents’ SSC result was significantly associated with the locality and quality of classrooms whereas HSC result was significantly affected by computer and internet facilities as well as the overall quality of services/facilities they enjoyed in their colleges.